Adaptações curriculares e a inclusão educacional da pessoa em situação de deficiência: um estudo de caso em escolas públicas localizadas no município de Belém/PA - PAULA, Hulda Iza Gonçalves de (Universidade Federal do Pará, 2017)
This work is part of the theme of Educational Inclusion of the person's disability status. It is case study results conducted in two public schools in the municipality of Belém do Pará in which we analyze how these have promoted large curriculum adaptations to meet the demands of educational inclusion of people in disability situation. We had as objectives in this study to analyze the large curriculum adaptations implementation process promotes educational inclusion, access and permanence of the person in a situation of disability in public schools in the city of Belém / PA and discuss on actions that schools surveyed they have made effective to ensure access to the curriculum and the educational inclusion of these people. We also seek to analyze on how to position the educators working in public schools studied regarding the need to promote curricular adaptations for educational inclusion of people in disability situation. In this study the methodological procedures used during the research were qualitative approach through desk research, observation and semi-structured interviews with teachers, coordinators and managers of the surveyed schools. The collected data were analyzed using content analysis method. As theoretical assumptions we orient ourselves from the social model of disability, also making an analysis of documents from the National Curriculum Standards for the Curricular Adaptations strategies for the education of students with special educational needs. While results of this study we list the schools surveyed have implemented palliative settings within the adequacy of its physical spaces, structural and resources to promote educational inclusion, the adjustments, however, do not meet the demand of the needs of students in a situation of disabilities enrolled in them, especially in the categories spaces, affordable furniture and accessibility features. In this regard, public investment factor emerged as crucial for schools to develop the necessary adjustments to promote access and inclusion of all students. In factor access to the curriculum the curricular adaptation actions carried out in the schools surveyed are focused on evidence adaptations, reviews and content directed to students in deficiency situation, measures, however, that are not shielded and not provided for in the pedagogical proposal of both schools which does not guarantee its implementation and does not define how to give them the process. Educators of the schools surveyed consider that the curricular adaptation actions are associated with the process of teaching and learning, therefore, it is the responsibility of teachers to implement them. Large curricular adaptations constitute as adopted measures to enable the educational inclusion in the surveyed schools, although whatsoever in these schools differently Brazilian official view.